Application and validation of the surface-to-underground transient electromagnetic method for detecting deep water-rich area affected by shallow aquifers: a case study of the Ningdong mining area - Li, Maofei; Dou, Zhonghao; Jiang, Zhihai; Yu, Juan; Xiao, Luping (Frontiers in Earth Science, 2025)
Water-rich area present underground in coal mines pose a serious threat to the safety of coal mining operations. Electrical methods are commonly used for the detection of subsurface water-rich area, but the presence of shallow aquifers can significantly affect the accuracy of deep water-rich zone detection. In this study, surface-to-underground transient electromagnetic (SUTEM) technology and the finite-difference time-domain (FDTD) method was employed to investigate the detection of deep water-rich areas under the low-resistivity shielding of shallow aquifers. On the basis of the theoretical analysis, numerical simulation, and practical application results, it was concluded that variations in the thickness and depth of shallow aquifers have a certain effect on the transient electromagnetic (TEM) response. Compared with surface TEM, SUTEM can obtain more geological information about deep water-rich area when affected by shallow aquifers, allowing for a more accurate delineation of low-resistivity anomaly area. Therefore, SUTEM can serve as a method for the detection of deep water-rich area in coal mines under similar geological conditions.